Multi-scale top-down approach for modelling epileptic protein-protein interaction network analysis to identify driver nodes and pathways. (October 2020) - Suresh, Nikhila T.; E.R., Vimina; U., Krishnakumar
Highlights: The result revealed eight pivotal genes like DNM1, CCND1, ITPR1, HRAS, SRC, BRAF, CREBBP & SPTAN1 present in epilepsy. This study identified pathways like PI3 kinase, VEGF, CCKR, Ras, PDGF, Integrin, Wnt, TGF-beta, EGF receptor signaling etc. Functional enrichment analysis discloses critical tasks during neuron excitation as a dominating function in epileptic state. Validation of key epileptic genes & linked-up pathways are investigated using clinical level results and Gene Ontology (GO). Abstract: Protein - Protein Interaction Network (PPIN) analysis unveils molecular level mechanisms involved in disease condition. To explore the complex regulatory mechanisms behind epilepsy and to address the clinical and biological issues of epilepsy, in silico techniques are feasible in a cost- effective manner. In this work, a hierarchical procedure to identify influential genes and regulatory pathways in epilepsy prognosis is proposed. To obtain key genes and pathways causing epilepsy, integration of two benchmarked datasets which are exclusively devoted for complex disorders is done as an initial step. Using STRING database, PPIN is constructed for modelling protein-protein interactions. Further, key interactions are obtained from the established PPIN using network centrality measures followed by network propagation algorithm -Random Walk with Restart (RWR). The outcome of the method reveals some influential genes behind epilepsy prognosis, along with their associated pathways like PI3 kinase, VEGF signaling, Ras, Wnt signaling etc. In comparison with similar works, our results have shown improvement in identifying unique molecular functions, biological processes, gene co-occurrences etc. Also, CORUM provides an annotation for approximately 60% of similarity in human protein complexes with the obtained result. We believe that the formulated strategy can put-up the vast consideration of indigenous drugs towards meticulous identification of genes encoded by protein against several combinatorial disorders.